Pig Management and Biosecurity Measures against African Swine-Fever (ASF) Disease: After the outbreak in Lagos State - Omodewu, Ifeoluwa A.; Oluwole, Olufunke O.; Idowu, Ayodeji; Oyegbami, Ajoke; Bolaji, Afolarin (Syiah Kuala University, 2025)
This study identified management and biosecurity measures taken against ASF disease before and after the outbreak. A total of one hundred and twenty (120) pig farmers from fifteen communities represented the sample population in Lagos State. A structured questionnaire was used to gather information from farmers, and the data obtained were analyzed using descriptive statistics. The results showed that about 34% of respondents experienced the disease outbreak for the first time, while 66% had previously witnessed an outbreak. However, only 53.3% of the total respondents had experienced an ASF outbreak within the last three years. Management-wise, the majority of farms (90.8%) practiced an intensive management system, while the remaining 9.2% practiced a semi-intensive system. Most farmers (69.7%) sourced their water from boreholes. For health and safety, 35.5% of farmers reported burying their waste. Thirty-eight percent (38%) of respondents claimed occasional use of veterinary services for their livestock. It can be deduced from this study that a lack of adequate knowledge and training on biosecurity, the indiscriminate purchase of stock without quarantining, and reliance on water sources other than boreholes predisposed farmers to the disease. In conclusion, farmers are encouraged to establish strict biosecurity protocols, consistently use veterinary services, and ensure appropriate waste disposal to prevent contracting and spreading the disease.